Mapping Potential Locations of Reservoir Development Planning Based on Biogeophysical Conditions in Bulok Watershed of Lampung Province - Amini, Rosidah; Yuwono, Slamet Budi; Kusumastuti, Dyah Indriana; Riniarti, Melya; Banuwa, Irwan Sukri; Wahono, Endro Prasetyo (The University of Lampung, 2022)
Floods and droughts are problems that threaten the success of agricultural crops. The reservoir can be used as a water management system that can anticipate these problems. This study aims to examine the potential location of the reservoir development planning based on biogeophysical conditions in the Bulok Watershed of Lampung Province, which uses the overlay method and weighting and scoring techniques developed by Geographic Information System (GIS). The population covers the entire biogeophysical area of the Bulok watershed, with samples of 4 biogeophysical parameters, namely land cover, slope, soil conditions and geological conditions. The results showed that the distribution of land cover types that dominate in the Bulok watershed is mixed dry land agriculture. The most common slopes are flat to wavy slopes. The soil types that dominates are soils with andesite lithology, basalt, diorite, fine-grained tefra, and coarse-grained tefra. The geological formation that dominates is the Hulu Simpang Formation. Based on the 4 biogeophysical parameters selected in the study, there are 69 locations with great potential for planning the construction of reservoirs in the Bulok watershed. 20 points are spread over the administrative area of Tanggamus Regency, 23 points in Pringsewu Regency, and 26 points in Pesawaran Regency. Of the 87.670 ha of Bulok watershed area, 14.192 ha is very potential location area. Keywords: Biogeophysical Conditions, Potential Locations, Reservoir